2019
DOI: 10.3390/medicines6010019
|View full text |Cite
|
Sign up to set email alerts
|

Search for Drugs Used in Hospitals to Treat Stomatitis

Abstract: Stomatitis is an inflammatory disease of the oral mucosa, often accompanied by pain. Usually it is represented by aphthous stomatitis, for which treatment steroid ointment is commonly used. However, in the cases of refractory or recurrent stomatitis, traditional herbal medicines have been used with favorable therapeutic effects. Chemotherapy, especially in the head and neck region, induces stomatitis at higher frequency, which directly affects the patient’s quality of life and treatment schedule. However, effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Hara et al showed that among 18 Kampo medicines, HST is most frequently used in Japan, possibly due to the presence of glycyrrhiza that contains anti-inflammatory glycyrrhizin. It was surprising that HST had not been used in China [5]. Traditional medicines have been prescribed to elders and adults rather than children, but inclusion of sweet licorice as an ingredient will make it easier for children to take [5].…”
Section: Kampo Medicine and Constitutive Plant Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hara et al showed that among 18 Kampo medicines, HST is most frequently used in Japan, possibly due to the presence of glycyrrhiza that contains anti-inflammatory glycyrrhizin. It was surprising that HST had not been used in China [5]. Traditional medicines have been prescribed to elders and adults rather than children, but inclusion of sweet licorice as an ingredient will make it easier for children to take [5].…”
Section: Kampo Medicine and Constitutive Plant Extractsmentioning
confidence: 99%
“…It was surprising that HST had not been used in China [5]. Traditional medicines have been prescribed to elders and adults rather than children, but inclusion of sweet licorice as an ingredient will make it easier for children to take [5].…”
Section: Kampo Medicine and Constitutive Plant Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, frequent and long-term exposure to these drugs may further lead to more adverse effects and often drug resistance. 6,7 Natural medicines have become increasingly used in many countries. These become popular among consumers who search for natural ways as an alternative therapy and the general feeling that natural medicines are safer than synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Oral mucositis is one of the most common complications during chemotherapy and some local radiotherapies that can give significant effect on continuation of the therapy. Oral mucositis results in erythema and ulceration of the non-keratinized mucosa, causing suffering pain, decrease in nutritional intake, and bloodstream infections [ 1 , 2 , 3 ]. In general, the etiology of chemotherapy-induced mucositis can be divided into two main causes.…”
Section: Introductionmentioning
confidence: 99%